2018
DOI: 10.1002/chem.201705640
|View full text |Cite
|
Sign up to set email alerts
|

Photocytotoxic Copper(II) Complexes with Schiff‐Base Scaffolds for Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a promising and minimally invasive method for the treatment of superficial diseases, and photosensitizers with high phototoxicity indices (defined as (IC )/(IC )) are essential for the development of ideal photosensitizing properties for this technology. Herein, we report a series of photocytotoxic copper(II) complexes [Cu( QYMP)(dppn)] ( QYMP=N,N,O-tridentate Schiff-base derivatives, dppn=benzo[i]dipyrido[3,2-a;2',3'-c]phenazine), the structures of which have been confirmed by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Phototoxic Cu( ii ) complexes with Schiff base ligands were also designed for PDT applications ( Cu-8 ). 124 Cu-8 was quite cytotoxic upon visible light irradiation in human squamous carcinoma cells (SCC15) and in basal carcinoma cells (BCC) and less toxic in the dark. The charge transfer from the phenolate π orbitals to the metal dπ* orbitals is responsible for a visible LMCT absorption band.…”
Section: Phototoxic First-row Transition Metal Complexesmentioning
confidence: 99%
“…Phototoxic Cu( ii ) complexes with Schiff base ligands were also designed for PDT applications ( Cu-8 ). 124 Cu-8 was quite cytotoxic upon visible light irradiation in human squamous carcinoma cells (SCC15) and in basal carcinoma cells (BCC) and less toxic in the dark. The charge transfer from the phenolate π orbitals to the metal dπ* orbitals is responsible for a visible LMCT absorption band.…”
Section: Phototoxic First-row Transition Metal Complexesmentioning
confidence: 99%
“…4 Consequently, Schiff base complexes have raised interest in various fields of research and found applications in many areas, includ ing catalysis, 5 molecular magnetism, 6 spin crossover, 7 sensing, 8 nonlinear optical (NLO) molecular materials, [9][10][11][12] porous 13 and energy materials, 14 as well as for their properties in biologica l, pharmacological and medicinal chemistry. [15][16][17][18][19] In this regard, palladium(II) complexes with Schiff base ligands have been intensively investigated due to their applications in catalysis and in a wide variety of biological reactions. They have indeed been used as homogeneous and heterogeneous catalysts, especially in Suzuki-Miyaura cross coupling reaction, [20][21][22] and as antiviral, anti-fungal, anti-microbial and anti-tumor bioinorganic agents, [23][24][25][26][27][28] respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Copper is a nontoxic and bioessential element that is vital to the health of all living organisms, and therefore, photochemotherapeutic usage of different copper complexes is an interesting field of research (75,76). The photodynamic activity of copper(II) complexes: [Cu(L 1 )B]ClO 4 and [Cu(L 2 )B]ClO 4 ( where L 1 = 2‐[(pyridin‐2‐yl)methyleneamino]phenol, L 2 = 2‐[(pyridin‐2‐yl)methyleneamino]benzenethiol, and B is 1 H‐imidazo[4,5‐f][1,10]phenanthroline and 1‐(pyren‐2‐yl)‐ 1 H‐imidazo[4,5‐f][1,10]phenanthroline, was studied in a structure–activity relationship (SAR)‐based approach.…”
Section: Coppermentioning
confidence: 99%